Desain Karakter untuk Board Game Edukasi Burung Endemik - Biantoro, Zahranie Suga Eka Putri; Masnuna; El Chidtian, Aileena Solicitor Costa Rica (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2025)
Indonesia possesses a rich in natural resources, including the presence of various endemic bird species. However, there endemic birds are currently facinng serious threats due to widespread habitat destruction and illegal wildlife trade. This condition necessitates increased public attention and awareness from an early age. To foster such awareness, it is necessary to develop educational media that are attractive and aligned with children’s interest. This study aims to design characters for an educational board game with the theme of conserving and introducing endemic birds, targeted at children age 13-15 years. The method used in this study are qualitative annd quantitative. The study resulted in the creation of four main characters, Pak Damar (Forest Ranger), Mbak Rani (Bird Researcher), Mas Budi (Environmental Activist), and Dokter Tari (Wildlife Veterinarian), each design based on children’s visual preferences. The characters developed for this board game are expected to provide an enjoyable learninng experience while enhancinng early awareness of endemic bird conservation among young audiences.